Effects of Workpiece Surface and Cutting Parameters on the Finished Surface Quality in Turning Based on Finite Element Method - Ho, Ngoc The Quang; Do, Thanh Trung (Journal of Technical Education Science, 2023)
Turning is a traditional and widely used machining process in the manufacturing industry. The finished surface quality is one of the most important factors in determining the quality of the product and the effectiveness of the machining process. The surface quality is affected by several factors such as workpiece surface, cutting parameters and tool stiffness. Also, the finite element method is a powerful tool to analyze these factors and optimize the process parameters to achieve the desired surface finish. Therefore, in this study, the different values of wavelength (s), cutting speed (v), cutting feed (f) and stiffness of toolholder (Kx) were considered by using simulation method. Then, the surface roughness values (Rz) were determined from the different between the average value of the five tallest profile peak height and the average value of the five deepest profile valley in the finished surface. The results showed that the cutting feed was a main parameter that effected on the surface roughness (Rz) in the metal turning process. Also, the optimal value of surface roughness was achieved when s = 0.05 mm, f = 0.3 - 0.4 mm/rev, Kx = 4 - 6 e8N/m and v = 190 m/min. The findings of this study can be helpful in selecting the surface quality of the workpiece, determining the sequence of machining steps and choosing the cutting parameters to achieve both high productivity and the desired surface quality of turning products.